Hydrothermal Synthesis of Barium Titanate: Effect of Titania Precursor and Calcination Temperature on Phase Transition - Sasirekha, Natarajan; Rajesh, Baskaran (Industrial & engineering chemistry research, 2008)
Nanosized barium titanate powders were synthesized by a hydrothermal method. The effect of titania precursors on the phase transition of BaTiO3 with respect to Ba/Ti ratio, reaction temperature, reaction time, and calcination temperature was investigated. The synthesized materials were characterized by X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. BaTiO3 in pure cubic phase with spherical morphology was observed with a lower calcination temperature, Ba/Ti ratio, reaction temperature, and time. Increase in the tetragonal phase was ascertained in treatments at higher reaction temperature with a longer reaction time. The lattice hydroxyl release is believed to be the reason for tetragonality at high reaction and calcination temperatures. To prepare tetragonal BaTiO3 using HClO4-TiO2, the optimum synthesis conditions viz., Ba/Ti ratio, reaction temperature, and reaction time, are 1.2, 160 °C, and 3 h, respectively, at a calcination temperature of 1150 °C. The reaction time and reaction temperature for the cubic−tetragonal phase transformation of BaTiO3 shifted toward shorter reaction time and lower reaction temperature when TiO2 was synthesized by hydrolysis using HClO4 as the acid catalyst.